2017
DOI: 10.20472/ss2017.6.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of National Policy Toward Providing Low Cost Housing in Malaysia

Abstract: Abstract:Providing housing for the low income group (LIG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…According to the PUPR Ministry, there are 11 million households that do not have proper housing in Indonesia (Fallahi, 2017). This figure consists of 7.6 million homeownership backlogs and 2.3 million uninhabitable houses.…”
Section: Introductionmentioning
confidence: 99%
“…According to the PUPR Ministry, there are 11 million households that do not have proper housing in Indonesia (Fallahi, 2017). This figure consists of 7.6 million homeownership backlogs and 2.3 million uninhabitable houses.…”
Section: Introductionmentioning
confidence: 99%
“…Several local and international research studies can be located on low-income housing, housing affordability, and housing and welfare (Fallahi 2017;Iheme et al 2015). However, housing policy evaluations, which holistically explore all three (03) above research areas, were not found.…”
mentioning
confidence: 99%